Transversals of Geometric Objects and Anagram-Free Colouring - Bazargani, Saman (Université d'Ottawa / University of Ottawa, 2023)
This PhD thesis is comprised of 3 results in computational geometry and graph theory. In the first paper, I demonstrate that the piercing number of a set S of pairwise intersecting convex shapes in the plane is bounded by O(\alpha(S)), where \alpha(S) is the fatness of the set S, improving upon the previous upper-bound of O(\alpha(S)^2). In the second article, I show that anagram-free vertex colouring of a 2\times n square grid requires a number of colours that increases with n. This answers an open question in Wilson's thesis and shows that even graphs of pathwidth 2 do not have anagram-free colouring with a bounded number of colours. The third article is a study on the geodesic anagram-free chromatic number of chordal and interval graphs. \emph{Geodesic anagram-free chromatic number} is defined as the minimum number of colours required to colour a graph such that all shortest paths between any pair of vertices are coloured anagram-free. In particular, I prove that the geodesic anagram-free chromatic number of a chordal graph G is 32p'w, where p' is the pathwidth of the subtree intersection representation graph (tree) of G, and w is the clique number of G. Additionally, I prove that the geodesic anagram-free chromatic number of an interval graph is bounded by 32p, where p is the pathwidth of the interval graph. This PhD thesis is comprised of 3 results in computational geometry and graph theory.
Keywords: Helly's Theorem; Piercing points; Fatness; Pairwise intersecting; Anagram-free; Transversals; Treewidth; Pathwidth; Chordal Graphs; Interval Graphs; Geodesic Anagram-Free Chromatic Number; 2xn Grid